Strategi Bertahan Pengemudi Ojol di Masa Pandemi Covid-19 di Kota Makassar - Nur Damayanti (Universitas Muslim Maros, 2021)
The online motorcycle taxi application (ojol) has become one of the most widely used applications by the people of Indonesia. However, since the outbreak of Covid-19 in Indonesia, including Makassar, something has been